Carbon-supported ruthenium-based catalyst as well as preparation method and application thereof
By supporting Ru3+ ions on microporous carbon, the carbon-supported ruthenium-based catalysts is solved, and the existing homogeneous catalysts are difficult to recycle in the CO2 hydrogenation process to formic acid is achieved, and efficient and stable catalyst circulation performance and low-cost industrial application are achieved.
Patent Information
- Application Number
- CN202411969007.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
It is difficult for existing homogeneous catalysts to achieve effective recycling of catalysts in CO2 hydrogenation to formic acid reaction, resulting in limited application of their applications in industrial production.
Microporous carbon-supported Ru3+ ions are used to prepare microporous carbon by sintering soluble carbohydrates, and Ru3+ ions are supported by a simple and easy preparation method to form a catalyst with high catalytic activity and excellent cycle stability.
It has achieved a high-efficiency reaction of catalyzed carbon dioxide hydrogenation to formic acid. The cycling performance of the catalyst is as high as 95%, it can be reused multiple times and its activity remains stable, reducing production costs and having good promotion and application prospects.
Smart Images

Figure CN119746852A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic chemical synthesis, and specifically relates to a carbon-supported ruthenium-based catalyst and a preparation method and application thereof. Background Art
[0002] At present, the conversion of CO2 into small molecule products (such as synthesis gas, methanol, dimethyl ether, formic acid, low-carbon hydrocarbons, etc.) and other products with higher added value and greater market potential through catalytic conversion has become an important way to eliminate and utilize CO2. Formic acid, as a basic chemical raw material, is widely used in organic synthesis, printing and dyeing, boots and leather, food, etc. The direct synthesis of formic acid from CO2 hydrogenation is not only an atom-economical reaction, but also requires low energy consumption. It is an effective way to rationally utilize carbon dioxide and one of the chemical fixation conversion methods. At present, the catalysts for the hydrogenation of CO2 to produce formic acid and its derivatives at home and abroad are mainly homogeneous complex catalysts. For example, Matthias Beller, Henrik Junge and others from the Leibniz Institute for Catalysis in Germany reported a system for the reversible hydrogenation of CO2 to produce formic acid by promoting α-amino acids in Nature Energy, 2022, 7(5): 438-447. The system uses Mn-pincer complex as a homogeneous catalyst, in which the total turnover number (TON) of CO2 hydrogenation to produce formate is 2,000,000. Although the homogeneous catalyst has high activity, the separation and recovery of the catalyst after the reaction is a difficulty that is difficult to overcome in industrial production, resulting in poor recycling of the catalyst. Summary of the invention
[0003] In view of the shortcomings of the existing methods, the present invention provides a carbon-supported ruthenium-based catalyst and a preparation method and application thereof.
[0004] To achieve the above object, the present invention adopts the following technical solution:
[0005] In a first aspect, the present invention provides a carbon-supported ruthenium-based catalyst, comprising a carrier and an active component supported on the carrier, wherein the carrier is microporous carbon prepared by sintering soluble sugars, and the active component is Ru 3+ ions, the Ru 3+ The mass of the ions is 1% to 3% of the mass of the carrier.
[0006] Preferably, the soluble sugar is one or more of d-glucose, pentose and starch.
[0007] In a second aspect, the present invention provides a method for preparing a carbon-supported ruthenium-based catalyst, comprising the following steps:
[0008] Soluble sugars are mixed with ZnCl2, put into a tube furnace, calcine under a nitrogen atmosphere, and then grind, wash, and dry to obtain microporous carbon; then, a solvent, RuCl3·3H2O, and the above microporous carbon are put into a beaker, stirred at room temperature, and then washed and dried to obtain the product.
[0009] Preferably, the mass ratio of the soluble sugar to ZnCl2 is 1:2-4.
[0010] Preferably, the calcination conditions are: heating to 700°C to 1100°C at a heating rate of 1° to 5° / min and calcining for 1 to 3 hours.
[0011] Preferably, the ratio of RuCl3·3H2O, microporous carbon and solvent is 0.5-1.6 mg: 15-25 mg: 5-10 mL.
[0012] In a third aspect, the present invention provides an application of a carbon-supported ruthenium-based catalyst in the catalytic hydrogenation of carbon dioxide to produce formic acid.
[0013] Preferably, the application includes: loading a carbon-supported ruthenium-based catalyst, deionized water and triethylamine into a high-pressure reactor, washing and blowing the high-pressure reactor with CO2 gas to replace the air in the reactor, sequentially introducing liquefied CO2 and H2 into the high-pressure reactor, performing hydrogenation reaction under stirring conditions, and cooling and releasing the pressure after the reaction is completed.
[0014] Preferably, the usage ratio of triethylamine, deionized water and carbon-supported ruthenium-based catalyst is: 1-3 mL: 5-10 mL: 5-20 mg.
[0015] Preferably, the hydrogenation reaction temperature is 100-120° C., the pressure is 3-6 MPa, and the reaction time is 1-12 h.
[0016] The positive beneficial effects of the present invention are:
[0017] 1. Microporous carbon loaded with Ru in the present invention 3+ The catalyst is used in the reaction of hydrogenation of carbon dioxide to formic acid. The microporous carbon is prepared by the sintering process of soluble sugars, forming a rich microporous structure, which is convenient for loading a large amount of Ru 3+ Ions, the preparation method of the catalyst of the present invention is simple and easy, low in cost, has high catalytic activity and excellent cycle stability, and after five repeated reactions, its cycle performance is as high as 95%, and it can be reused many times with stable activity. In addition, the reaction conditions for catalytic hydrogenation of carbon dioxide to formic acid are mild and the reaction time is short, which greatly reduces the production cost and has a good prospect for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1The SEM images of the carbon-supported ruthenium-based catalysts prepared in Examples 1 to 5 of the present invention, with Figures af corresponding to Examples 1 to 5;
[0019] Figure 2 N2 adsorption-desorption isotherms (a) and pore size distribution (b) of carbon-supported ruthenium-based catalysts prepared in Examples 1 to 5 of the present invention;
[0020] Figure 3 This is a cycle data diagram of the carbon-supported ruthenium-based catalyst prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0021] The present invention is further described below in conjunction with some specific embodiments.
[0022] Example 1
[0023] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0024] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 700 ° C at a heating rate of 3 ° / min and calcined for 2 h. After calcination, the sample was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0025] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0026] Example 2
[0027] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0028] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 800 ° C at a heating rate of 3 ° / min and calcined for 2 h. After calcination, the sample was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0029] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0030] Example 3
[0031] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0032] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 900 ° C at a heating rate of 3 ° / min and calcined for 2 h. After calcination, the sample was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0033] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0034] Example 4
[0035] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0036] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 3° / min and calcined for 2 hours. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0037] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0038] Example 5
[0039] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0040] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1100°C at a heating rate of 3° / min and calcined for 2h. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0041] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0042] Example 6
[0043] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0044] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 3° / min and calcined for 2 hours. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0045] S2. Weigh 5.3 mg of RuCl3·3H2O and 200 mg of microporous carbon support into a beaker containing 50 mL of methanol, stir at room temperature for 1 h, and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0046] Example 7
[0047] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0048] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 3° / min and calcined for 2 hours. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0049] S2. Weigh 15.9 mg of RuCl3·3H2O and 200 mg of microporous carbon support into a beaker containing 50 mL of methanol, stir at room temperature for 1 h, and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0050] Example 8
[0051] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0052] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:2 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 3° / min and calcined for 2h. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0053] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0054] Example 9
[0055] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0056] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:4 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 3° / min and calcined for 2h. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0057] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0058] Example 10
[0059] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0060] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 1° / min and calcined for 2 hours. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0061] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0062] Embodiment 11
[0063] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0064] S1, soluble sugar d-glucose and ZnCl2 were physically mixed in a mass ratio of 1:3 and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 1000°C at a heating rate of 5° / min and calcined for 2h. The sample after calcination was a black block solid, which was then ground, filtered, washed and dried with deionized water to obtain a microporous carbon carrier;
[0065] S2. Weigh 10.6 mg of RuCl3·3H2O and 200 mg of microporous carbon support and add them to a beaker containing 50 mL of methanol. Stir for 1 h at room temperature and then filter and wash with deionized water to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst.
[0066] Comparative Example 1
[0067] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0068] Weigh 10.6 mg of RuCl3·3H2O and 200 mg of commercial carbon nanotube CNT carrier into a beaker containing 50 mL of methanol, stir at room temperature for 1 h, and then centrifuge to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst Ru / CNT with a Ru loading of 2%.
[0069] Comparative Example 2
[0070] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0071] Weigh 10.6 mg of RuCl3·3H2O and 200 mg of commercial mesoporous carbon MC into a beaker containing 50 mL of methanol, stir at room temperature for 1 h, and then centrifuge to remove the weakly bound Ru. 3+ , and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst Ru / MC with a Ru loading of 2%.
[0072] Comparative Example 3
[0073] A method for preparing a carbon-supported ruthenium-based catalyst comprises the following steps:
[0074] Weigh 10.6 mg RuCl3·3H2O and 200 mg commercial carbon black MA carrier into a beaker containing 50 mL methanol, stir at room temperature for 1 h, and then centrifuge to remove the weakly bound Ru. 3+, and then dried at 60°C for 24h to obtain a carbon-supported ruthenium-based catalyst Ru / MA with a Ru loading of 2%.
[0075] SEM images of Ru / C prepared at different calcination temperatures in Examples 1 to 5 are shown in Figure 1 , nitrogen adsorption and desorption curves and pore size distribution diagrams are shown in Figure 2 a and 2b, the BET test results of the specific surface areas of the carbon-supported ruthenium-based catalysts obtained in Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Table 1.
[0076] Depend on Figure 1 It can be seen that the SEM test was carried out on the catalysts prepared at different calcination temperatures. The catalyst of the present invention is in the shape of tiny blocks, so that Ru is fully dispersed.
[0077] Depend on Figure 2 As can be seen from Table 1, the catalysts prepared at different calcination temperatures were subjected to BET tests to obtain nitrogen adsorption and desorption curves and pore size distribution diagrams. The catalysts of the present invention are mainly micropores. The specific surface area of the catalyst prepared in Example 4 is significantly larger than that of the catalysts in other examples and the comparative catalyst, proving that it has the largest number of micropores.
[0078] Applying the carbon-supported ruthenium-based catalysts prepared in the above-mentioned Examples 1 to 11 and Comparative Examples 1 to 3 to hydrogenate carbon dioxide to produce formic acid comprises the following steps:
[0079] A 50 mL high-pressure reactor was used, and 5 mg of carbon-supported ruthenium-based catalyst, 6 mL of deionized water and 1.2 mL of triethylamine were placed in it. The reaction mixture was gently shaken to mix the reagents and the catalyst evenly. The high-pressure reactor was flushed with CO2 gas to replace the air in the reactor. Liquefied CO2 was introduced into the high-pressure reactor. When the pressure of the high-pressure reactor reached 3 MPa, H2 was introduced into the high-pressure reactor again after the air pressure stabilized so that the total pressure of the high-pressure reactor reached a total pressure of 6 MPa. The high-pressure reactor was then heated to a reaction temperature of 120°C, and the stirring rate was set to 800 r / min. After reacting for 12 hours, the reactor was cooled and the pressure was released. After the reaction, the reactor was rapidly cooled, and the liquid product containing the suspended catalyst was collected and filtered through a 0.2 μm filter. The formate concentration was determined using a high performance liquid chromatography (HPLC) system (YL 9100Plus, YL Instruments Co., Ltd) equipped with a UV detector and an Aminex HPX-87H column. The operating temperature was 30°C and 0.6 mL of a 5 mM H2SO4 solution was used as the eluent. The test results are shown in Table 1.
[0080] Wherein: The activity evaluation index of the catalyst adopts the conversion number (TON) of the target product formate and is calculated by the following formula:
[0081] TON=N HCOO- / N Ru
[0082] N HCOO - : the amount of formate produced in the reaction (mol); N Ru : The active component of the catalyst used in the reaction is Ru 3+ The amount of substance of the ion (mol);
[0083] Formate concentration (mol / L) = N HCOO - / V 产物 .
[0084] Table 1 Carbon dioxide hydrogenation to formic acid reaction results
[0085]
[0086]
[0087] As shown in Table 1, from the test results of Examples 1 to 5, it can be seen that the optimal calcination temperature of the present invention is 1000°C in Example 4; from the test results of Examples 4, 6 to 7, it can be seen that the optimal Ru 3+ The mass of the ions is 2% of the mass of the carrier; from the test results of Examples 4, 8 to 9, it can be seen that the optimal mass ratio of d-glucose to ZnCl2 of the present invention is 1:3; from the test results of Examples 4, 10 to 11, it can be seen that the optimal heating rate of the present invention is 3° / min. The catalytic effect of the carbon-supported ruthenium-based catalyst of the present invention is better than that of Comparative Examples 1 to 3, and the conversion number of formate of the present invention can be as high as 10696.
[0088] The carbon-supported ruthenium-based catalyst prepared in Example 4 was used for a cyclic stability test, and the operating steps were as follows: a 50 mL high-pressure reactor was used, 20 mg of the carbon-supported ruthenium-based catalyst in Example 4 was weighed, 6 mL of deionized water and 1.2 mL of triethylamine were measured and loaded into the high-pressure reactor, and gently shaken to mix the reagents and the catalyst evenly, the high-pressure reactor was washed with CO2 gas to replace the air in the reactor, and liquefied CO2 was introduced into the high-pressure reactor. When the pressure of the high-pressure reactor reached 3 MPa, after the air pressure stabilized, H2 was introduced into the high-pressure reactor again to make the total pressure of the high-pressure reactor reach a total pressure of 6 MPa, and then the high-pressure reactor was heated to a reaction temperature of 120°C, and the stirring rate was set to 800 r / min. After reacting for 1 hour, the pressure was released by cooling. After the reaction, the reactor was rapidly cooled, and the liquid product containing the suspended catalyst was collected and filtered through a 0.2 μm filter. After each run, the catalyst was separated by filtration, washed with 50 mL of water and acetone, and dried under vacuum at 60°C before the next run. The stability of the catalyst was tested in five consecutive runs. The collected liquid product was measured for formate concentration by a high performance liquid chromatography (HPLC) system (YL 9100Plus, YL Instruments Co., Ltd) equipped with a UV detector and an Aminex HPX-87H column. The operating temperature was 30°C and 5 mM H2SO4 solution (0.6 mL) was used as the eluent. The test results are shown in Table 2 and Figure 3 .
[0089] Table 2 Cyclic stability test results of carbon-supported ruthenium-based catalysts
[0090] Cycle times <![CDATA[Ru 3+ Ion loading %]]> Formate concentration mol / L TON 1 2 0.73 1778 2 2 0.73 1763 3 2 0.71 1733 4 2 0.71 1715 5 2 0.70 1697
[0091] As shown in Table 2, the carbon-supported ruthenium-based catalyst prepared in Example 4 is applied to the reaction of hydrogenating carbon dioxide to produce formic acid. The reaction lasts for 1 hour each time. The activity of the catalyst is still very stable in five consecutive runs. Figure 3 It can be seen that according to the fifth conversion data, the reaction activity is still as high as 95% of the first reaction, which proves the excellent ability of the carbon-supported ruthenium-based catalyst of the present invention in terms of cyclic stability.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A carbon-supported ruthenium-based catalyst, characterized in that: The invention comprises a carrier and an active component loaded on the carrier, wherein the carrier is microporous carbon prepared by sintering soluble sugars, and the active component is Ru 3+ ions, the Ru 3+ The mass of the ions is 1% to 3% of the mass of the carrier.
2. The carbon-supported ruthenium-based catalyst according to claim 1, characterized in that The soluble sugar is one or more of d-glucose, pentose and starch.
3. A method for preparing a carbon-supported ruthenium-based catalyst according to claim 1 or 2, characterized in that: The steps include: Soluble sugars are mixed with ZnCl2, put into a tube furnace, calcine under a nitrogen atmosphere, and then grind, wash, and dry to obtain microporous carbon; then, a solvent, RuCl3·3H2O, and the above microporous carbon are put into a beaker, stirred at room temperature, and then washed and dried to obtain the product.
4. The method for preparing a carbon-supported ruthenium-based catalyst according to claim 3, characterized in that: The mass ratio of the soluble sugar to ZnCl2 is 1:2-4.
5. The method for preparing a carbon-supported ruthenium-based catalyst according to claim 3, characterized in that: The calcination conditions are: heating to 700°C-1100°C at a heating rate of 1°-5° / min and calcining for 1-3h.
6. The method for preparing a carbon-supported ruthenium-based catalyst according to claim 3, characterized in that: The ratio of RuCl3·3H2O, microporous carbon and solvent is 0.5-1.6 mg: 15-25 mg: 5-10 mL.
7. Application of a carbon-supported ruthenium-based catalyst in the catalytic hydrogenation of carbon dioxide to produce formic acid.
8. The use according to claim 7, characterized in that: include: A carbon-supported ruthenium-based catalyst, deionized water and triethylamine are loaded into a high-pressure reactor, the high-pressure reactor is purged with CO2 gas to replace the air in the reactor, liquefied CO2 and H2 are introduced into the high-pressure reactor in sequence, hydrogenation reaction is carried out under stirring conditions, and the pressure is released by cooling after the reaction is completed.
9. The use according to claim 8, characterized in that: The dosage ratio of the triethylamine, deionized water and carbon-supported ruthenium-based catalyst is: 1-3 mL: 5-10 mL: 5-20 mg.
10. The use according to claim 9, characterized in that: The hydrogenation reaction temperature is 100-120° C., the pressure is 3-6 MPa, and the reaction time is 1-12 hours.
Citation Information
Patent Citations
Ru / MWCNTs catalyst and preparing method thereof
CN103464149A
Application of supported Ru-based catalyst
CN103864597A
Carbon-supported multi-component catalyst and preparation method and application thereof
CN105214686A
Method for preparing formate / formic acid through CO2 hydrogenation reduction under catalysis of ruthenium complexes in water phase
CN108424359A
Application of supported nano ruthenium catalyst in preparation of formate from carbon dioxide or bicarbonate
CN117776898A